Proteomic analysis reveals potential exosomal biomarkers in patients with sporadic Alzheimer disease - Plaschke, Konstanze; Kopitz, Jürgen; Gebert, Johannes; Wolf, Nadine D.; Wolf, Robert Christian (Alzheimer disease & associated disorders, 2023)
Background: Despite substantial progress made in the past decades, the pathogenesis of sporadic Alzheimer disease (sAD) and related biological markers of the disease are still controversially discussed. Cerebrospinal fluid and functional brain imaging markers have been established to support the clinical diagnosis of sAD. Yet, due to the invasiveness of such diagnostics, less burdensome markers have been increasingly investigated in the past years. Among such markers, extracellular vesicles may yield promise in (early) diagnostics and treatment monitoring in sAD. - Materials and Methods: In this pilot study, we collected the blood plasma of 18 patients with sAD and compared the proteome of extracted extracellular vesicles with the proteome of 11 age-matched healthy controls. The resulting proteomes were characterized by Gene Ontology terms and between-group statistics. - Results: Ten distinct proteins were found to significantly differ between sAD patients and controls (P<0.05, False Discovery Rate, corrected). These proteins included distinct immunoglobulins, fibronectin, and apolipoproteins. - Conclusions: These findings lend further support for exosomal changes in neurodegenerative disorders, and particularly in sAD. Further proteomic research could decisively advance our knowledge of sAD pathophysiology as much as it could foster the development of clinically meaningful biomarkers.
Gesehen am 19.07.2024